The feature selection problem in computer-assisted cytology - Kowal, Marek; Skobel, Marcin; Nowicki, Norbert (Zielona Góra: Uniwersytet Zielonogórski)
Modern cancer diagnostics is based heavily on cytological examinations. Unfortunately, visual inspection of cytological preparations under the microscope is a tedious and time-consuming process. Moreover, intra- and inter-observer variations in cytological diagnosis are substantial. Cytological diagnostics can be facilitated and objectified by using automatic image analysis and machine learning methods. Computerized systems usually preprocess cytological images, segment and detect nuclei, extract and select features, and finally classify the sample.
Keywords: nuclei segmentation; feature selection; classification; breast cancer; convolutional neural networks